- #1

- 2

- 0

[tex] \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2} [/tex]

**Solution 1**: Standard trigonometric substitution: [tex] x=\sin\theta [/tex]

Integral becomes

[tex] \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2}=\int^{\sin^{-1}\frac{1}{\sqrt{2}}}_{\sin^{-1}0}\frac{d\theta}{\cos\theta}\sqrt{1-\sin^2\theta}=\int^{\pi/4}_0d\theta=\frac{\pi}{4} [/tex]

**Solution 2**: Integration by parts gives:

[tex] \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2}=\left.x\sqrt{1-x^2}\right|^{\frac{1}{\sqrt{2}}}_0 + \int^{\frac{1}{\sqrt{2}}}_0dx\frac{x^2}{\sqrt{1-x^2}}=\frac{1}{2}+\int^{\frac{1}{\sqrt{2}}}_0dx \frac{x^2}{\sqrt{1-x^2}} [/tex]

Adding to the right hand side:

[tex] 0=\int^{\frac{1}{\sqrt{2}}}_0dx\frac{1}{\sqrt{1-x^2}}-\int^{\frac{1}{\sqrt{2}}}_0dx\frac{1}{\sqrt{1-x^2}} [/tex]

we get:

[tex] \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2}=\frac{1}{2} - \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2}+\int^{\frac{1}{\sqrt{2}}}_0dx\frac{1}{\sqrt{1-x^2}} [/tex]

or rearranging:

[tex] \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2}=\frac{1}{4}+\frac{1}{2}\int^{\frac{1}{\sqrt{2}}}_0dx \frac{1}{\sqrt{1-x^2}} [/tex]

Finally since:

[tex] \sin^{-1} x=\int^x_0\frac{dz}{\sqrt{1-z^2}}\quad |x|\leq1 [/tex]

we find:

[tex] \int^{\frac{1}{\sqrt{2}}}_0dx\sqrt{1-x^2}=\frac{1}{4}+\frac{1}{2}\sin^{-1}\frac{1}{\sqrt{2}}=\frac{1}{4}+\frac{\pi}{8} [/tex]

Any illuminating comments are appreciated.

Regards,

Beauty